Chemical, Physical and Sensory Characteristics of Powdered Drinks in Various Formulations of Pineapple Juice and Sweet Orange Juice - Astuti, Sussi; Mutiara Jayanti, Rienda; Nurainy, Fibra; Rizal, Samsul; Widaputri, Silaturahmi; Indraningtyas, Lathifa (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
Fruit powdered drink products can be made by combining pineapple juice (SN) and sweet orange juice (SJ). This study aims to evaluate the chemical, physical, and organoleptic characteristics of powder beverages with various SN and SJ compositions, and determine the optimal formulation. The research method used a Complete Randomized Block Design (CRBD) with one factor repeated four times. The factor studied was the ratio of SN and SJ in six levels: 100%:0% (P1), 80%:20% (P2), 60%:40% (P3), 40%:60% (P4), 20%:80% (P5), and 0%:100% (P6). Data were analyzed using analysis of variance (ANOVA) and followed by Least Significant Difference (LSD) test at 5% significance level. Results showed that SN and SJ combinations significantly influenced chemical, physical and sensory parameters. The P5 formulation (20% SN: 80% SJ) was selected as the optimal treatment with the best characteristics across all tested parameters.